E-Archeo Project: The 3D Reconstruction of the Roman Villae in Sirmione and Desenzano (Brescia, Italy) - Patrizia Basso; Barbara Bianchi; Daniele Bursich; Nicola Delbarba; Alessandra Marinello; Fiammetta Soriano (Applied System Innovation, 2023)
The e-Archeo project, commissioned from ALES S.p.A.by the Ministry of Culture (MIC), aims to valorise the multimedia experience of eight Italian archaeological sites. This paper discusses the University of Verona’s contribution to this project, which focuses on the virtual reconstruction of two Roman villas located in Sirmione and Desenzano (Lombardy). This paper outlines the 3D survey methodologies and scientific back-end approach using Extended Matrix. The architectural and decorative reconstruction process for each site is elucidated, providing a comprehensive understanding of the process followed. Furthermore, the University developed a narrative to accompany virtual visits. One of the main project outputs was e-Archeo 3d, a virtual reality web app that allows remote and on-site use.